STUDY ON THE DEVELOPMENT STRATEGY OF ALOE VERA PROCESSED PRODUCTS (A CASE STUDY OF SRI REJEKI URBAN FARMING GROUP, CIPTOMULYO VILLAGE, SUKUN SUBDISTRIC, MALANG CITY) - Muhammad, Miqdad; Shiddieqy, Firman Ash; Meitasari, Deny; Laili, Fitrotul; Angelika, Miranda Aurelia (Socio-Economics/Agribusiness Department, 2024)
This study aims to formulate a business development strategy as well as determine the alternative approach that should be prioritized by the Sri Rejeki urban farming group in Ciptomulyo Village, Sukun Subdistrict, Malang City, which is fostered by PT Pertamina Patra Niaga FT Malang through the Corporate Social Responsibility (CSR) program. Sri Rejeki urban farming group is active in aloe vera development from production to processed products. Primary data for this study was gathered through Focus Group Discussions (FGD) with group members and interviews with the Head of the Ciptomulyo village. The study employs a qualitative methodology. Strength, Weakness, Opportunity, and Threat (SWOT) analysis, the IE matrix, the IFAS and EFAS matrices, and the Quantitative Strategy Planning Matrix (QSPM) are all used in the analysis process. According to the IE matrix, the Sri Rejeki urban farming group is in cell V (Hold and Maintain). Based on the SWOT analysis, 9 potential strategies were determined. According to the QSPM matrix, the urban farming organization Sri Rejeki should emphasize Strategy 2, creating processed aloe vera goods for the Malang City souvenir market and branding products through social media, with a total TS score of 5.11. The implementation of this plan is projected to benefit both the local economy and the well-being of group members. Aside from that, it is intended that the outcomes of this study would become a basis for decision-making for groups, stakeholders, and partners to develop and prioritize mentoring programs, as well as support the sustainability of the CSR program by PT Pertamina Patra Niaga FT Malang for the urban farming group Sri Rejeki.